ANALISIS PERAMALAN PENJUALAN AYAM DENGAN MENGGUNAKAN METODE MOVING AVERAGE DAN EXPONENTIAL SMOOTHING DI CV. TABASSAM AZ ZUFAR JOMBANG: ANALISIS PERAMALAN PENJUALAN AYAM DENGAN MENGGUNAKAN METODE MOVING AVERAGE DAN EXPONENTIAL SMOOTHING DI CV. TABASSAM AZ ZUFAR JOMBANG - David Ari fianto; Fatma Ayu N.F.A; Tri Rijanto (INVANTRI (Inovasi Dan Pengelolaan Industri), 2023)
In this modern era of the technology, the rapid development of the business world and the demand of product that required by consumer is very high also. Therefore, the company must be able to make an optimal planning, there is in the planning of production or planning of demand to make the company can achieve the objectives targeted. To achieve it, the company have to forecast the amount of selling or consumer’s demand about product or services produced. The CV. Tabassam Az-Zufar Jombang is a company that engaged in the partnership of boiler chicken farms. One of analysis that can be used to forecast is the moving average and the exponential smoothing method. The aims of this research are the first is to know the chicken sales forecasting in the periods of June 2018 until July 2018 and the second is to know the accuratest of the sales forecasting method. The method that will be used to this research is the moving average and exponential smoothing method. The result of the research showed that the smallest error value of method is SES method with α = 0,7 where is the value of MAD is 23.384, MSE = 1.096.023.269, and MAPE = 16 %. As for result of the chicken sales forecasting using the single exponential smoothing method with α = 0,7 in June 2018 is 207.758 tails and July is 207.758 tails.